Postponing Retirement and Social Security in a Two Sector Model - Partha Sen (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Pay-as-you-go (PAYG) social security schemes in the OECD countries are facing solvency problems, as people are living longer and birth rates have declined. Postponing the full retirement age (FRA), when retirees are entitled to full pension, has been proposed as a solution. This effectively lowers the payroll tax rate since pension is paid only in the post-FRA period. In a two-period two-sector overlapping generations model, I show that this shift lowers savings (because a part of the expected old age income is consumed in the first period), as employment increases. In the transition to the new steady state, capital is decumulated and the wage rate falls. Contrast this with a reduction of the payroll tax rate where the initial old suffer reduced consumption, but the young have higher post-tax income and this spurs capital accumulation.
Keywords: H55; 330; overlapping generations; social security reform; postponing retirement